The majority of murine γδ T cells at the maternal–fetal interface in pregnancy produce IL‐17. Issue 7 (31st May 2016) - Pinget, Gabriela V; Corpuz, Theresa M; Stolp, Jessica; Lousberg, Erin L; Diener, Kerrilyn R; Robertson, Sarah A; Sprent, Jonathan; Webster, Kylie E
Abstract : Compared with lymphoid tissues, the immune cell compartment at mucosal sites is enriched with T cells bearing the γδ T‐cell receptor (TCR). The female reproductive tract, along with the placenta and uterine decidua during pregnancy, are populated by γδ T cells predominantly expressing the invariant Vγ6 + Vδ1 + receptor. Surprisingly little is understood about the function of these cells. We found that the majority of γδ T cells in the non‐pregnant uterus, pregnant uterus, decidua and placenta of mice express the transcription factor RORγt and produce interleukin‐17 (IL‐17). In contrast, IFNγ‐producing γδ T cells were markedly reduced in gestational tissues compared with uterine‐draining lymph nodes and spleen. Both uterine‐resident invariant Vγ6 + and Vγ4 + γδ T cells which are more typically found in lymphoid tissues and circulating blood, were found to express IL‐17. Vγ4 + γδ T cells were particularly enriched in the placenta, suggesting a pregnancy‐specific recruitment or expansion of these cells. A small increase in IL‐17‐producing γδ T cells was observed in allogeneic compared with syngeneic pregnancy, suggesting a contribution to regulating the maternal response to paternally‐derived alloantigens. However, their high proportions also in non‐pregnant uteri and gestational tissues of syngeneic pregnancy imply a role in the prevention of intrauterine infection or quality control of fetal development. These data suggest the need for a more rigorous evaluation of the role of IL‐17 in sustaining normal pregnancy, particularly as emerging data points to a pathogenic role for IL‐17 in pre‐eclampsia, pre‐term birth, miscarriage and maternal immune activation‐induced behavioral abnormalities in offspring.